2013
DOI: 10.1126/science.1234274
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization of GABAergic Inhibition by Dendritic Spines

Abstract: GABAergic inhibition plays a critical role in shaping neuronal activity in the neocortex. Numerous experimental investigations have examined perisomatic inhibitory synapses, which control action potential output from pyramidal neurons. However, most inhibitory synapses in the neocortex are formed onto pyramidal cell dendrites, where theoretical studies suggest they may focally regulate cellular activity. The precision of GABAergic control over dendritic electrical and biochemical signaling is unknown. Using ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
297
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(314 citation statements)
references
References 42 publications
15
297
1
1
Order By: Relevance
“…At the subcellular level, somatostatinexpressing (Sst) interneuron inhibitory synapses placed along the dendritic tree of a pyramidal neuron can veto synaptic integration (2) and Ca 2+ electrogenesis (3, 4) with fine spatiotemporal specificity (5). Recent studies in several neocortical areas have highlighted the participation of superficial layer 2/3 (L2/3) Sst interneurons in a canonical disinhibitory circuit supporting context-dependent sensory processing, in which the activity of L2/3 Sst interneurons is suppressed by the action of interneuron-selective vasoactive intestinal peptide-expressing (Vip) interneurons (6).…”
mentioning
confidence: 99%
“…At the subcellular level, somatostatinexpressing (Sst) interneuron inhibitory synapses placed along the dendritic tree of a pyramidal neuron can veto synaptic integration (2) and Ca 2+ electrogenesis (3, 4) with fine spatiotemporal specificity (5). Recent studies in several neocortical areas have highlighted the participation of superficial layer 2/3 (L2/3) Sst interneurons in a canonical disinhibitory circuit supporting context-dependent sensory processing, in which the activity of L2/3 Sst interneurons is suppressed by the action of interneuron-selective vasoactive intestinal peptide-expressing (Vip) interneurons (6).…”
mentioning
confidence: 99%
“…We could therefore use a much lower concentration that has minimal inhibitory action on GABA A receptors and does not cause firing pattern change (18,48). In our experimental conditions, it was difficult to predict the exact final concentration of caged glutamate in vivo, but potential disinhibition by CDNI-Glu may have changed the magnitude of Ca 2+ rise in local dendritic spines and facilitated LTP in the network (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
“…Author Manuscript CDNI-GABA was, in fact, the first caged GABA probe reported to be effective for 2P optoneurobiology [15] , and is starting to be used for biological studies [21,22] , therefore we compared the 2P-evoked currents from this probe with G5-DEAC450-GABA. We have found that we can very reliably elicit GABAergic currents from 2P uncaging along he main apical dendrite of CA1 neurons [18] .…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…Since our antagonism data suggests the cloaked caged GABA is essentially inert up to about 0.6 mM ( Figure 2) we bath applied the probe to brain slices at this concentration. We did this because we knew CDNI-Glu is best used at about 1 mM [21,[23][24][25][26] , and has an IC 50 = 0.24 mM for GABA-A receptor blockade [18] . Thus, we patch-clamped a CA1 neuron and monitored voltage changes produced by two-color, 2P uncaging.…”
mentioning
confidence: 99%